PROSPEK PERLINDUNGAN PENYANDANG DISABILITAS TERHADAP PERILAKU DISKRIMINATIF DI KOTA SEMARANG - Lita Tyesta ALW (Faculty of Law, Universitas Diponegoro, 2015)
This research aims to determine the prospects of persons with disabilities protection against discriminatory behavior in Semarang. The research method is normative using the laws approach (statutory approach), and the conceptual approach (conceptual approach). Results of the study found that the government of Semarang have prospects in providing protection and fulfillment of the rights of persons with disabilitas of discriminatory behavior. Constitution of the Republic of Indonesia Act1945 does not set a specific reference on Disability, but set firmly and clearly regarding non- discrimination, equality before the law, and the right to receive equal treatment before the law throughout Indonesia.